BCAS: A blockchain-based ciphertext-policy attribute-based encryption scheme for cloud data security sharing. (March 2021) - Zuo, Yuting; Kang, Zhaozhe; Xu, Jian; Chen, Zhide
It is the most important and challenging problem to share the data safely in cloud computing. Some so-called trusted third parties may also infringe users' data privacy. It is an urgent problem for data owners to share data safely with the designated users rather than the third party or other users. Traditional encryption schemes utilize different keys to produce multiple encrypted copies of the same data for users. It is no longer applicable for cloud data sharing security. Attribute-based encryption can solve above problems, but it needs to rely on trusted third parties to protect the users' privacy. In this article, in order to address the above problems, we propose a blockchain-based ciphertext-policy attribute-based encryption scheme for cloud data secure sharing without relying on any trusted third parties. Blockchain-based ciphertext-policy attribute-based encryption scheme can protect the rights and security of data owner. Compared with existing cloud security schemes, the proposed scheme has more advantages in terms of the six aspects: (1) data owners have the authority to decide who can decrypt the data; (2) the operations of users are retained permanently, and all records are tamper-proof; (3) our proposed scheme has the characteristic of "one-to-many" encryption, and data is encrypted only once; (4) our scheme does not rely on any trusted third party; (5) in terms of the discrete logarithm problem and decisional q parallel-bilinear Diffie–Hellman exponent problem, we prove that our proposed scheme is secure; and (6) experiment shows that our proposed scheme is more efficient than the comparative scheme.